Hidden Depths The Origins of Human Connection - Spikins, Penny (White Rose University Press, 2022)
In Hidden Depths, Professor Penny Spikins explores how our emotional connections have shaped human ancestry. Focusing on three key transitions in human origins, Professor Spikins explains how the emotional capacities of our early ancestors evolved in response to ecological changes, much like similar changes in other social mammals. For each transition, dedicated chapters examine evolutionary pressures, responses in changes in human emotional capacities and the archaeological evidence for human social behaviours. Starting from our earliest origins, in Part One, Professor Spikins explores how after two million years ago, movement of human ancestors into a new ecological niche drove new types of collaboration, including care for vulnerable members of the group. Emotional adaptations lead to cognitive changes, as new connections based on compassion, generosity, trust and inclusion also changed our relationship to material things. Part Two explores a later key transition in human emotional capacities occurring after 300,000 years ago. At this time changes in social tolerance allowed ancestors of our own species to further reach out beyond their local group and care about distant allies, making human communities resilient to environmental changes. An increasingly close relationship to animals, and even to cherished possessions, appeared at this time, and can be explained through new human vulnerabilities and ways of seeking comfort and belonging. Lastly, Part Three focuses on the contrasts in emotional dispositions arising between ourselves and our close cousins, the Neanderthals. Neanderthals are revealed as equally caring yet emotionally different humans, who might, if things had been different, have been in our place today. This new narrative breaks away from traditional views of human evolution as exceptional or as a linear progression towards a more perfect form. Instead, our evolutionary history is situated within similar processes occurring in other mammals, and explained as one in which emotions, rather than 'intellect', were key to our evolutionary journey. Moreover, changes in emotional capacities and dispositions are seen as part of differing pathways each bringing strengths, weaknesses and compromises. These hidden depths provide an explanation for many of the emotional sensitivities and vulnerabilities which continue to influence our world today.